2022
DOI: 10.1017/s003329172200335x
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment, migration and risk of first-episode psychosis: results from the multinational EU-GEI study

Abstract: Background Child maltreatment (CM) and migrant status are independently associated with psychosis. We examined prevalence of CM by migrant status and tested whether migrant status moderated the association between CM and first-episode psychosis (FEP). We further explored whether differences in CM exposure contributed to variations in the incidence rates of FEP by migrant status. Methods We included FEP patients aged 18–64 years in 14 European sites and recruited controls representative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Childhood maltreatment, which mainly includes physical, sexual and emotional abuse and neglect, is common worldwide with pediatric prevalence rates of 13-36% (Lim, Howells, Radua, & Rubia, 2020). These adverse early-life experiences involved bio-psycho-social mediators and moderators (Sideli et al, 2020), and have been suggested to be closely related with cognitive decline, attention impairment, emotional dysregulation, and reward anticipation disorder (Hart et al, 2018;Lim et al, 2016), and may even increase the risks of suffering from mental illness, such as posttraumatic stress disorder (PTSD) (Daniels, Lamke, Gaebler, Walter, and Scheel, 2013), major depressive disorder (MDD) (Goltermann et al 2022;Guo et al 2022;Haidl et al 2021), borderline personality disorder (Herzog, Kube, & Fassbinder, 2022), schizophrenia (Cancel, Dallel, Zine, El-Hage, & Fakra, 2019;D'Andrea et al, 2022;Sideli et al, 2020), substance abuse (Hughes et al, 2017), eating disorders (Cascino et al, 2022;Luo et al, 2020), as well as functional somatic and visceral pain syndromes (Chandan et al, 2020). Neurobiology changes of the brain might underlie the occurrence of the above symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood maltreatment, which mainly includes physical, sexual and emotional abuse and neglect, is common worldwide with pediatric prevalence rates of 13-36% (Lim, Howells, Radua, & Rubia, 2020). These adverse early-life experiences involved bio-psycho-social mediators and moderators (Sideli et al, 2020), and have been suggested to be closely related with cognitive decline, attention impairment, emotional dysregulation, and reward anticipation disorder (Hart et al, 2018;Lim et al, 2016), and may even increase the risks of suffering from mental illness, such as posttraumatic stress disorder (PTSD) (Daniels, Lamke, Gaebler, Walter, and Scheel, 2013), major depressive disorder (MDD) (Goltermann et al 2022;Guo et al 2022;Haidl et al 2021), borderline personality disorder (Herzog, Kube, & Fassbinder, 2022), schizophrenia (Cancel, Dallel, Zine, El-Hage, & Fakra, 2019;D'Andrea et al, 2022;Sideli et al, 2020), substance abuse (Hughes et al, 2017), eating disorders (Cascino et al, 2022;Luo et al, 2020), as well as functional somatic and visceral pain syndromes (Chandan et al, 2020). Neurobiology changes of the brain might underlie the occurrence of the above symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…2022; Haidl et al . 2021), borderline personality disorder (Herzog, Kube, & Fassbinder, 2022), schizophrenia (Cancel, Dallel, Zine, El-Hage, & Fakra, 2019; D'Andrea et al, 2022; Sideli et al, 2020), substance abuse (Hughes et al, 2017), eating disorders (Cascino et al, 2022; Luo et al, 2020), as well as functional somatic and visceral pain syndromes (Chandan et al, 2020). Neurobiology changes of the brain might underlie the occurrence of the above symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although we adjusted by the most relevant confounders in the field of trauma, cannabis and psychosis literature, the interplay between trauma and other environmental variables such as migration or discrimination is difficult to disentangle and was not the focus of the current paper. A recent publication on this topic from our group is already available (D'Andrea et al, 2022 ). We hope other factors such as the genetic influence in the form of family history and polygenic risk scores can be explored in the future and has not been focus of the current work either.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated rates of NAPD have been reported in young refugees resettled in several high-income countries [ 5 7 ] and in other groups of migrants and descendants of migrants [ 8 10 ]. Childhood trauma has been shown to be associated with psychosis in both retrospective and prospective studies [ 11 , 12 ] and is particularly prevalent among youth who have been forcibly displaced [ 13 , 14 ]. But exposure to other risk factors in the aetiology of psychosis including experiences of discrimination, socio-economic adversity, social isolation and distress [ 15 , 16 ] are more widespread across groups of migrants and minorities.…”
Section: Introductionmentioning
confidence: 99%